Audit quality, audit committee, media exposure, and Corporate Social Responsibility - Rawi Rawi; Munawar Muchlish (Jurnal Siasat Bisnis, 2022)
Purpose: The specific purpose of this research can be developed more specifically to identify the influence of audit quality, audit committee, and media exposure on Corporate Social Responsibility. Corporate Social Responsibility is a social responsibility that is beneficial for the company itself, the local community as well as the community in general. Corporate Social Responsibility is basically a form of obligation and commitment of the company to pay attention to the interests of stakeholders for the sake of sustainable economic development in improving the quality of life.Design/methodology/approach: This research used secondary data in the form of annual report of basic and chemical industry manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019, with data sources accessed from www.idx.co.id. The sample withdrawal in this research used Purposive Sampling method which is a technique of determining samples with certain considerations, samples used as many as 120 samples. The analysis method used multiple linear analysis and t-test hypothesis.Findings: The results showed that Audit Quality, Audit Committee, and Media Exposure had a partial positive effect on Corporate Social Responsibility. CSR is a form of commitment to business activities to act ethically, contribute to economic development, and improve the quality of life of workers and communities.Research limitations/implications: The implications of research results, the higher the audit quality, the larger the number of audit committees and the higher the intensity of using the website in media exposure at the company, the greater the company in CSR disclosure.Practical implications: Practical implications for investors, that the integrity of financial statements can be trusted by investors as investment decision making, while for companies/management, will get a positive value from the public regarding broad CSR disclosures.Originality/value: This research is different from the previous research on the object of research and the most recent observation throughout the year. Thus, it can add the latest CSR research references by the development of CSR.